2013
DOI: 10.36366/frontiers.v23i1.327
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Global Awareness over Short-Term Study Abroad Sequence: A Factor Analysis

Abstract: Over the past 10 years, U.S. undergraduate participation in study abroad has increased dramatically.  The majority of these study abroad experiences have durations of less than eight weeks.  Due to the rapid growth in both of these areas, there has been increased interest in assessing student outcomes associated with short-term study abroad (STSA) programs.  This paper investigates the impact of an STSA experience on undergraduate students' levels of global awareness over the entire STSA sequence: pre-preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…This feeling of connectedness may be influenced by the level of political and geographic isolation of U.S. students from other places of the world [65]. These findings provide context for why U.S. students who travel and study abroad gain a deeper sense of international understanding and global awareness [66][67][68]. Many U.S.-based students are engaging with the YouthMappers network remotely from their home sites in the U.S.…”
Section: Discussionmentioning
confidence: 95%
“…This feeling of connectedness may be influenced by the level of political and geographic isolation of U.S. students from other places of the world [65]. These findings provide context for why U.S. students who travel and study abroad gain a deeper sense of international understanding and global awareness [66][67][68]. Many U.S.-based students are engaging with the YouthMappers network remotely from their home sites in the U.S.…”
Section: Discussionmentioning
confidence: 95%
“…However, we also found a great deal of variation in faculty members' goals, particularly by discipline; and seven faculty members noted on the survey that they specifically did not focus on cultural learning in their courses. This variation on goals may be one of the reasons why we see such variation in the research literature on the outcomes of short-term study abroad programs (e.g., Anderson et al, 2006;Chieffo & Griffiths, 2004;Coker et al, 2018;Gullekson et al, 2011;Kurt et al, 2013). If intercultural learning is not the central goal of a course, we would not expect to see significant gains in students' intercultural competence resulting from participation in that course.…”
Section: Discussionmentioning
confidence: 97%
“…Although there has been a dramatic increase in participation in short-term study abroad programs, particularly faculty-led programs (Institute of International Education, 2018; Tuma, 2007), research is mixed on whether or not these programs are achieving the desired outcomes. Several studies have found positive outcomes including increased intercultural awareness (Chieffo & Griffiths, 2004), global awareness (Kurt, Olitsky, & Geis, 2013), and intercultural development (Gullekson, Tucker, Coombs Jr, & Wright, 2011). In a study looking particularly at faculty-led short-term study abroad programs, Gaia (2015) found that students in these programs showed enhanced cultural understanding and awareness and a willingness to interact with people from other cultures.…”
Section: Faculty-led Short-term Study Abroad Coursesmentioning
confidence: 99%
“…: Campbell-Price, 2014; DeMello, 2011), or surveys that required participants to self-identify perceived learning during their international experiences (e.g. : Deloach et al, 2015;Kurt et al, 2013;Van "T Klooster, 2014), the results of this research are based on the quantitative analysis of 1152 participants, 989 of whom had participated in international tourism. In doing so, the study provides empirical evidence to support the underpinning assumption of IET that it encourages global learning.…”
Section: Discussionmentioning
confidence: 99%
“…International education theory has as its core the assumption that international travel, with its concomitant exposure to other cultures, nationalities and environments, is a highly desirable endeavour. International education proponents attest that it has the potential to foster intercultural learning and development (Vande Berg et al, 2012: xiii), and to facilitate global learning through the development of global awareness (Kurt et al, 2013), global mindedness (DeMello, 2011) and global competence (Deardorff, 2014).…”
Section: International Educationmentioning
confidence: 99%